Killer landslides [videorecording (DVD)] - Clark, Liesl (WGBY DVD Collection, 2014)
In less than two minutes in March, a one-square-mile field of debris slammed into the Washington state community of Oso, killing 41 and destroying nearly 50 homes. Drawing on analyses of other recent landslides around the world, geologists are investigating what triggered the deadliest U.S. landslide in decades and whether climate change is increasing the risk of similar disasters around the globe.